EXPERIMENTAL STUDY OF FERROMAGNETIC CORE PARAMETERS INFLUENCE ON ELECTROMECHANICAL CHARACTERISTICS OF A LINEAR INDUCTION-DYNAMIC CONVERTER - V.F. Bolyukh (National Technical University "Kharkiv Polytechnic Institute", 2014)
Experimental studies of ferromagnetic core parameters action on electromechanical characteristics of a linear induction-dynamic converter are conducted. An experimental installation is designed and built to determine the converter electromechanical parameters during its operation. A ferromagnetic core with four radial slots made allows regulating the height of the base and the outer shell. The core geometric parameters providing the highest speed of the armature are specified. Under certain parameters, the ferromagnetic core increases the converter efficiency up to 50%. The experimental results confirm the analytical studies within 6 % error.